Pemanfaatan lahan Dusun di Wilayah Konservasi Hutan untuk Mendukung Ketahanan Pangan Keluarga : Suku Talang Mamak - Anto Ariyanto; Afni Zulkifli (Asosiasi Dosen Akuntansi Indonesia, 2022)
Maintaining food security in traditional communities in forest conservation villages is to use land in village yards/gardens to produce family food. The Sadan settlement is a hamlet in the Bukit Tigapuluh National Park (TNBT), and the people of this village depend heavily on the forest to support their family's economy. Adult men in the village make mandah (out) from the village and collect non-timber forest products such as resin, jernang, petai and others. Meanwhile, women and children live in the hamlet. Women in Sadan village, become partners in this community service activity. The residents of Sadan village have not optimally utilized the gardens/yards in the hamlet for production activities that have economic value through food crop cultivation activities. This is due to limited knowledge in harvesting and cultivation techniques. This community service activity aims to provide counseling, training and land use practices. The implementation of this service activity is carried out with an approach to counseling and demonstration methods. The results of this service have influenced changes in the knowledge and views of participants, especially the use of yard/garden land to meet family food.